PENGUJIAN PECKING ORDER THEORY PADA EMITEN SYARIAH DI BURSA EFEK INDONESIA PADA TAHUN 2015-2017 - Indah Sumayah Gasim; Maslichah Maslichah; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study was to examine the pecking order theory in explainingthe preferences of corporate funding decisions. This research was conducted onIslamic companies listed in the Indonesian Stock Exchange in 2015-2017. Thisresearch sample was determined by purposive sampling method. This study usesmultiple linear regression models. The results of this study conclude thatProfitability has a significant positive effect on leverage. Company size (Size)has a significant positive effect on leverage. And The Investment Opportunity Setdo not have a significant effect on leverage.Keywords: Profitability, Company size (Size), Investment Opportunity SetLeverage.